Peculiarities of the oxide plasma creation using carbonate compounds - Shariy, S.V.; Yuferov, V.B.; Shvets, M.O.; Korotkova, I.M.; Shapoval, A.M.; Tkachov, V.I. (Вопросы атомной науки и техники, 2018)
The process of obtaining oxide plasma from carbonate compounds of calcium CaCO₃ and neodymium Nd₂(CO₃)₃ was studied. The experiment was carried out on a two-stage plasma source with a reflective discharge. The experiment was conducted with the following parameters: a discharge voltage of 50…150 V, a current of 8…30 A, a magnetic field of 100…200 Oe, the pressure in the vacuum chamber is 3·10⁻³…3·10⁻⁴ Torr. The ratio of the ionization potentials φi and the dissociation energy ε of the oxide components in the plasma was taken into account when selecting materials and analyzing the experimental data. For various conditions of the plasma arc burning, an analysis was made for the composition of the plasma and the elemental composition of the deposited target surfaces based on the experimental data. Досліджувався процес отримання оксидної плазми з карбонатних з'єднань кальцію CaCO₃ та неодиму Nd₂(CO₃)₃. Експеримент проводився на двоступінчатому джерелі з відбивним розрядом. Напруга розряду 50…150 В, струм 8…30 А, магнітне поле 100…200 Е, тиск у вакуумній камері 3·10⁻³…3·10⁻⁴Торр. При виборі матеріалів та аналізі експериментальних даних враховувалося співвідношення потенціалу іонізації φi та енергії дисоціації ε оксидних компонент y плазмі. На підставі експериментальних даних для різних умов горіння плазмової дуги зроблено аналіз складу плазми і елементного складу напилених поверхонь мішеней. Исследовался процесс получения оксидной плазмы из карбонатных соединений кальция CaCO₃ и неодима Nd₂(CO₃)₃. Эксперимент проводился на двухступенчатом источнике с отражательным разрядом. Напряжение разряда 50…150 В, ток 8…30 А, магнитное поле 100…200 Э, давление в вакуумной камере 3·10⁻³…3·10⁻⁴Торр. При выборе материалов и анализе экспериментальных данных учитывалось соотношение потенциалов ионизации φi и энергии диссоциации ε оксидных компонент в плазме. На основании экспериментальных данных для различных условий горения плазменной дуги сделан анализ состава плазмы и элементного состава напыленных поверхностей мишеней.